Gene expression and Levels of Plasma Protein Tyrosine Phosphatase Non-Receptor Type 22 (PTPN22)in Pulmonary Tuberculosis Patients and their Household Contacts in Makassar, Indonesia (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The protein tyrosine phosphatase non-receptor type 22 (PTPN22) gen,has been involved inthe immune response to tuberculosis infection by affecting the inflammatory response and subsequent antimicrobial immunity. This study aims to determine the PTPN22 expression and differences in the levels ofPTPN22 in pulmonary TB patients (PTB) with household contacts and healthy control.Methods: We analyzed PTPN22 expression and the level of plasma PTPN22 from pulmonary tuberculosispatients (PTB), household contacts and healthy control using real time PCR and ELISA method.Results: ThirtyPTB, 30 household contacts and 30 control were involved in this study. Analysis of theassocation of PTPN22 gene expression against TB showed that PTPN22 gene expression was 7.3 timesupregulated compared to household contact and 12.1 times upregulated compared to healthy controls.Levelsof plasma PTPN22 in PTB: 10.0620 ng/ml, in Household contact: 6.7923 ng/ml and in control: 4.4293 ng/These values did not differ significantly between the patients, household contact and control.Conclusion: Our study results found that PTPN22 gene expression is significantly increased in PTB thanhousehold contact and control.Levels of plasma PTPN22 in PTB patientsdid not differ significantly than inhousehold contact and control.